Determination of selpercatinib, a RET kinase inhibitor, in rat plasma and its application to a pharmacokinetic study. (21st December 2020) - Wang, Wei; Shi, Liuhong; Jin, Luya; Wang, Kun
Abstract: Selpercatinib (LOXO‐292) is a selective and potent RET inhibitor. A highly sensitive, rapid and specific high‐performance liquid chromatography with tandem mass spectrometry (LC–MS/MS) method for quantification of selpercatinib in rat plasma is reported. The method was validated in terms of selectivity, linearity, accuracy and precision, extraction recovery and matrix effect, stability and carryover as per the US Food and Drug Administration guidelines for bioanalytical method validation. Selpercatinib was detected by an electrospray ionization interface under selective reaction monitoring conditions in the positive ion mode. The calibration curve was linear over the concentration range from 1 to 2000 ng/ml with r 2 = 0.9951. The intra‐ and inter‐batch accuracy values ranged from 97.45 to 100.97% and from 98.70 to 100.74% with coefficients of variation of 2.45–6.99% and 5.89–7.99%, respectively. The extraction recovery and IS‐normalized matrix factor were acceptable for the bioanalysis of selpercatinib. Additionally, selpercatinib was found to be stable under the detected conditions. It showed linear pharmacokinetic characteristics following oral administration to rats at 2.0–18.0 mg/kg. The results showed that the novel method for detecting selpercatinib in rat plasma could be successfully applied for quantification of selpercatinib in biosamples from nonclinical studies.